2018
DOI: 10.3390/su10124345
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Sharing Mechanisms for A Wood Forest Product Supply Chain under Carbon Cap-and-Trade

Abstract: We consider a wood forest product supply chain consisting of a forestry company and a wood forest products manufacturer, where the forestry company produces timber and forestry carbon sinks, and the manufacturer consumes timber and carbon emission rights. A Stackelberg model is adopted to investigate the forest scale and carbon emission reduction decisions of the supply chain. We design and analyze the carbon emission reduction cost-sharing (ERCS) mechanism and carbon sink cost-sharing (SCS) mechanism, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Meanwhile, for illustration purposes, we present a numerical example here. According to the actual situation of the carbon sink transaction and the relevant data in the literature [39], the values of the parameters are shown in Table 2. (2) dr/dθ 1 > 0, dr/dθ 2 < 0.…”
Section: Discussion and Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, for illustration purposes, we present a numerical example here. According to the actual situation of the carbon sink transaction and the relevant data in the literature [39], the values of the parameters are shown in Table 2. (2) dr/dθ 1 > 0, dr/dθ 2 < 0.…”
Section: Discussion and Numerical Analysismentioning
confidence: 99%
“…Both the scale of the carbon sink forest and the average carbon limit level affect the market price of the carbon sink: When the scale of the carbon sink forest expands, the forestry enterprise can provide more forestry carbon sinks, so the price of the forestry carbon sinks will drop. On the other hand, when the carbon limit policy of the government is looser, the market demand of the manufacturing enterprise will be smaller, the price will also drop [39]. Therefore, the carbon sink price is…”
mentioning
confidence: 98%
“…The number of CSR reports by Chinese companies increased by nearly 53% in the decade from 2006 to 2015 [1]. Increasing attention has been paid to CSR activities in China's capital market [2][3][4][5][6][7][8][9][10], and this increased attention has provided many opportunities for scholars to conduct quantitative research on CSR activities and related information disclosure activities based on China's capital market [11][12][13][14]. In this regard, a large number of studies have focused on the driving factors and economic consequences of CSR activities and related disclosure activities of Chinese companies, especially in the past five years.…”
Section: Introductionmentioning
confidence: 99%
“…Song and He [14] found that the decentralized supply chain can be coordinated by a freshness-keeping, cost-sharing, and revenue-sharing contract. Sun et al [15] designed and analyzed the carbon emission reduction cost-sharing and carbon sink costsharing contracts, respectively. Several incentive mechanisms were investigated by Yoo and Cheong [7] for collaborative product quality improvement in a buyer-driven supply chain, and the impacts of those mechanisms on supply chain performance are studied.…”
Section: Contract Design and Coordination Of A Supply Chainmentioning
confidence: 99%